El uso de los mapas temáticos en la enseñanza de la geografía física - Chamorro Granda, Maria Elizabeth; Jiménez Arévalo, Ginger Aracely (Machala, 2021)
The present degree work is based on the importance of the use of thematic maps in education, since it allows a significant cognitive development of geographical knowledge in students, therefore, it is essential that this material continue to be used by contributing in some way way in academic training. Therefore, the project has been developed with the objective of determining the importance of the use of thematic maps in the teaching of physical geography in 5th grade “B” students of the Zoila Ugarte de Landívar school; Since, the central hypothesis was the lack of use of cartography has generated that geographical knowledge is not developed significantly in students during the teaching of physical geography in students of the indicated institution. The methodology used in this work corresponds to a quasi-experimental investigation, supported by the analytical-synthetic method as well as complementary methods such as the historical-logical,bibliographic, hypothetical-deductive, comparative and statistical that allowed the collection of theoretical and empirical information. . The selected sample corresponds to 30 students and a teacher in the fifth year of basic education from the aforementioned school. The results obtained in the research show that teachers do not make use of thematic maps during the teaching of physical geography of the students, which allows to conclude that the classes are not very participatory and that the students do not acquire the contents in a meaningful way.
El presente trabajo de titulación se basa en la importancia del uso de los mapas temáticos en la educación, ya que permite un desarrollo cognitivo de conocimientos geográficos significativo en los estudiantes, por ende, es esencial que se siga dando uso de este material contribuyendo de alguna manera en la formación académica. Por ende, el proyecto se ha elaborado con el objetivo de determinar la importancia del uso de los mapas temáticos en la enseñanza de la geografía física en los estudiantes de 5to “B” de la escuela Zoila Ugarte de Landívar; puesto que, la hipótesis central fue la falta del uso de la cartografía ha generado que no se desarrolle conocimientos geográficos de manera significativa en los estudiantes durante la enseñanza de la geografía física en los estudiantes de la institución indicada. La metodología utilizada en el presente trabajo corresponde a una investigación cuasi experimental, apoyada del método analítico-sintético como también de los métodos complementarios como el histórico-lógico, bibliográfico, hipotético-deductivo, comparativo y estadístico que permitieron la recopilación de información teórica como empírica. La muestra seleccionada corresponde a 30 estudiantes y una docente de quinto año de educación básica de la escuela antes mencionada. Los resultados obtenidos en la investigación dan consigo que los docentes no hacen uso de mapas temáticos durante la enseñanza de la geografía física de los estudiantes, lo cual permite concluir que las clases sean pocas participativas y que los estudiantes no adquieran los contenidos de manera significativa.
Keywords: MAPA TEMATICO; GEOGRAFIA FISICA; CONTENIDO GEOGRAFICO; EXPERIENCIA SENSORIAL; MATERIAL DIDACTICO